¿Impa rtial Electoral Institutes?: Cases of Mexico and Guerrero State (Andamios, Revista de Investigación Social, 2013)
Considering the importance of electoral institutions in our country’s democratization process, this article seeks to empirically demonstrate, through two study cases, whether a partisan bias in decisions taken by the General Council as a group in a collegiate fashion exists or not. To achieve such task, we ponder the reactivation of federalism in the country and the method by which the Congress’s Lower Chamber designates electoral councillors, to later examine two scenarios: a plural Congress and a congressional majority, in order to establish if any relation exists between nonpartisanship and the integration of the legislative branch. To develop this analysis, a  nonpartisanship model was built in two phases, accounting origin and compliance of the position.
Keywords: Electoral Institutions; General Council; Nonpartisanship; Impartiality; Lower Chamber; Democracy